Economic issues and political conflict : US-Latin American relations - Dominguez, Jorge I., 1945- (Butterworths studies in international political economy., 1982)
Economic Issues and Political Conflict: US-Latin American Relations is a collaborated work from different experts that discusses the economic and political relations and policies of Latin American countries with the United States of America and how it changed over the years. The book covers topics such as the history of the US-Latin American economic policies; US policy in relation to the Latin American countries; and the attitudes of Latin American national businesses toward multinational enterprises. The book also covers the business policies, industrial exports, and trade negotiations of L.